2003
DOI: 10.1097/00001721-200306000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of venous thromboembolism in medical patients with enoxaparin

Abstract: The Medical Patients with Enoxaparin (MEDENOX) trial was a randomized, placebo-controlled study that defined the risk of venous thromboembolism (VTE) in acutely ill, immobilized, general medical patients and the efficacy of the low-molecular-weight heparin, enoxaparin, in preventing thrombosis. We performed a post-hoc analysis to evaluate the effect of 40 mg enoxaparin once daily on MEDENOX patient outcome in different types of acute medical illness (heart failure, respiratory failure, infection, rheumatic dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
155
1
16

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 246 publications
(176 citation statements)
references
References 15 publications
4
155
1
16
Order By: Relevance
“…Observations with diverticulitis were selected as a comparison group because they also had an inflammatory colorectal condition, although the process is localized as opposed to systemic as in UC. Observations with respiratory failure were selected as another comparison group because these are nonsurgical patients considered to be at high risk for venous thromboembolic events [7] and are recommended to receive routine thromboembolic prophylaxis when admitted to the hospital. The surgical groups included any observations with UC, diverticulitis, or colorectal cancer (ICD-9 CM code 153, 153.0-153.9, 154, 154.0, 154.1), which also had a procedure code for any colorectal operation (ICD-9 CM procedure code 457, 457.…”
Section: Identification Of Casesmentioning
confidence: 99%
“…Observations with diverticulitis were selected as a comparison group because they also had an inflammatory colorectal condition, although the process is localized as opposed to systemic as in UC. Observations with respiratory failure were selected as another comparison group because these are nonsurgical patients considered to be at high risk for venous thromboembolic events [7] and are recommended to receive routine thromboembolic prophylaxis when admitted to the hospital. The surgical groups included any observations with UC, diverticulitis, or colorectal cancer (ICD-9 CM code 153, 153.0-153.9, 154, 154.0, 154.1), which also had a procedure code for any colorectal operation (ICD-9 CM procedure code 457, 457.…”
Section: Identification Of Casesmentioning
confidence: 99%
“…Subgroup analyses of studies have confirmed that a wide range of moderate-to high-risk medical patients, in particular elderly patients and patients with heart failure or respiratory failure, benefit from thromboprophylaxis. 40 Parameters for selecting the appropriate patients to treat are shown in Table 4.…”
Section: B Which Patients Should Be Selected For Treatment?mentioning
confidence: 99%
“…It is generally accepted that patients with CHF are characterized by an increased risk of VTE. In various studies, the incidence of APE or deep vein thrombosis in the population of patients hospitalized due to CHF ranged from 4% to 14% [18][19][20]. In another study, the incidence of APE in a group of patients with CHF was 9.1% despite adequate use Table 6.…”
Section: Discussionmentioning
confidence: 99%